Philippine Technocracy as a Bulwark Against Corruption: The Promise and the Pitfall - Tadem, Teresa S. Encarnacion (Philippine Social Sciences Review; Volume 64, No. 1, Jan-Jun 2012, Ed. Eric Manalastas, 2012)
Although technocracy in general is associated with economic decision-making rather than the politics of governance, the Philippine experience has shown that much hope has also been pinned on the country’s economic technocrats to counter-act corruption in the country. This was seen during the martial law (1972 to 1986) and post-martial law periods (1986-onwards). A reason for this is that technocrats are regarded as professionals and experts in their fields, and more importantly, “apolitical”. Their main concern, therefore, is to make sure that their economic policies are to be implemented. They are, therefore, expected to confront obstacles to this including corruption. Thus, during the martial law period, they were looked upon, particularly by the Philippine business community as well as by the country’s major lending institutions, i.e., the International Monetary Fund (IMF) and the World Bank (IMF/World Bank) as a bulwark against corruption. The same perspective is also shared during the post-martial law period where the technocrats continue to be viewed as an obstacle to crony capitalism and patronage politics which persists to pervade Philippine society. This paper, therefore, argues that there are factors which facilitate as well as hinder the role of technocracy in this aspect. One is the nature of the political leadership, i.e., whether the president is corrupt or not; second is the role of the IMF/World Bank and/or external donors in asserting the need for good governance; third is the degree of the “politicization” of technocracy, e.g. the nature of their political mass base, and fourth is the degree to which Philippine society is willing to tolerate corruption in government. All these aspects to a certain extent are affected by the state of the country’s political and economic stability. By doing so, the paper hopes to address the conditions under which technocracy is able to provide a leverage against corruption as well as its limitations. It will reveal that although Philippine experts have failed to achieve their final goals to eliminate corruption, the increments have been gained and lessons have been learned in confronting patronage politics and crony capitalism.
Keywords: corruption, technocracy